2023
DOI: 10.1111/nicc.12899
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between alarm fatigue and burnout among critical care nurses: A cross‐sectional study

Abstract: BackgroundAlarm fatigue has significant negative impacts on nurses and patient safety. However, the relationship between alarm fatigue and burnout is still unclear.AimsThis study aimed to explore the relationship between alarm fatigue and burnout among critical care nurses.Study designA descriptive‐analytical cross‐sectional study design was used. Data were collected from five hospitals in mainland China between January 2022 and March 2022. A general information questionnaire, the Chinese version of the Intens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…However, on study in Saudi Arabia reported that CCNs experienced moderate alarm fatigue and moderate-to-high burnout. 15 Another study showed that working in ICUs is associated with high levels of stress, which can lead to decreased productivity and poor healthcare quality if not well handled. 30 Although these studies did not show the association between nationality and alarm fatigue, their findings indicate that Saudi Arabian CCNs may be overly stressed and exhausted, which may play a role in alarm fatigue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, on study in Saudi Arabia reported that CCNs experienced moderate alarm fatigue and moderate-to-high burnout. 15 Another study showed that working in ICUs is associated with high levels of stress, which can lead to decreased productivity and poor healthcare quality if not well handled. 30 Although these studies did not show the association between nationality and alarm fatigue, their findings indicate that Saudi Arabian CCNs may be overly stressed and exhausted, which may play a role in alarm fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…16 Consequently, the Joint Commission established the National Patient Safety Goals in 2014 to control and adjust the alarm safety standards. 16 The mean alarm score among Chinese critical care nurses was found to be 21.11 using the Alarm Fatigue Questionnaire (AFQ), 15 and the mean alarm score among Iranian nurses was found to be 19.08, indicating a moderate rank of alarm fatigue. 3 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the study also discovered that alarm fatigue decreases with increasing 13 years of work experience, consistent with the results of our study. The survey results conducted by Ding S et al 22 among 236 critical care nurses from five hospitals in China similarly indicated a moderate level of alarm fatigue among critical care nurses, with the majority of nurses experiencing moderate to high levels of occupational burnout.…”
Section: The Degree Of Nurses Machine Alarm Fatigue Needs Improvementmentioning
confidence: 96%
“…Of these, six originated from China to examine the knowledge, attitude, and practice regarding glycaemic control among ICU professionals, 11 to explore the relationship between alarm fatigue and burnout among critical care nurses, 12 to examine the association between shift work schedules, compensatory sleep, work-family conflict, and fatigue of shift-working nurses, 13 to investigate stakeholders' values and preferences regarding draft recommendations for adapted physical restraint guidelines, 14 to investigate the knowledge, attitudes, and practice of prone positioning of patients among ICU nurses working in COVID19 units, 15 and to analyse the reliability and validity of a competency evaluation model for front-line nursing staff during the outbreak of major infectious diseases. 16 From Turkey, one study 17 identified the skin problems related to using personal protective equipment by ICU nurses, and another study 18 examined the relationship between alarm fatigue and the tendency to make medical errors among ICU nurses.…”
mentioning
confidence: 99%